ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN DAN BUDAYA ORGANISASIONAL TERHADAP KINERJA PEGAWAI DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI MEDIASI (Studi pada Pegawai Negeri Sipil Kota Pekalongan ) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research is addressed to see how job characteristic, organizational culture and Organizational Citizenship Behavior ( OCB) on performance have impact to organization as a whole and influence performance all employees which is on finally will improve image an organization. Proportional  Random  Sampling  was  used  as  sampling  technique  with  sample  of 150 participants. Technique Analysis which is used in this research is examination of validity, and reliability examination of hypothesis by using program SPSS for Windows release 16.0. Results of this study  indicate  that  organizational  culture  and organizational citizenship behavior (OCB) effect on performance. Job characteristic no effect to performance.Pursuant to used empirik model can be explained that influence job characteristic to performance more effective passing OCB. While  influence organizational culture to performance more effective directly from passing OCB. Keywords :job characteristic, organizational culture, OCB and performance.